Singular case of the driving instructor: Temporal and topographical disorientation - Futamura, Akinori (Neurol Clin Neurosci, 2017)
Lesions of the medio‐parietal lobes are linked with topographical and temporal disorientation, and are of interest to understanding mental time. We examined a 39‐year‐old man who worked as a driving instructor before cerebral hemorrhage, and followed his case for 8 years including neuropsychological testing and brain imaging. The patient had mild anterograde episodic amnesia, but no semantic amnesia. He felt that time passed too quickly, and developed a compulsive routine to compensate, although he was able to count time at a normal speed. Furthermore, he was unable to accurately sketch the layout of his house and to make a cross‐reference type timetable for the future. Brain magnetic resonance imaging showed lesions of the left anterior–posterior cingulate gyrus, and N‐isopropyl‐[(123)I] p‐iodoamphetamine single‐photon emission computed tomography showed decreased blood flow mainly of the left medio‐parietal lobe.